2023
DOI: 10.1186/s12871-023-01969-6
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic effect of erector spinae plane block in adults undergoing laparoscopic cholecystectomy: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Laparoscopic cholecystectomy is the gold standard surgical procedure for treating gallstone disease. Despite it being minimally invasive, various medications and methods are used to alleviate postoperative pain, and some patients still experience moderate-to-severe pain. This is a crucial problem that must be solved to avoid chronic pain. As part of postoperative multimodal analgesia, regional block is being increasingly applied in surgery under ultrasound guidance. We aimed to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…However, our results contrast with results from a meta-analysis done on a composite of abdominal surgeries, where an ESPB was superior to a placebo block [ 2 ]. In other systematic reviews and meta-analyses for more specific abdominal interventions, the ESPB has also been shown to decrease postoperative pain scores, opioid consumption, and the incidence of PONV [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our results contrast with results from a meta-analysis done on a composite of abdominal surgeries, where an ESPB was superior to a placebo block [ 2 ]. In other systematic reviews and meta-analyses for more specific abdominal interventions, the ESPB has also been shown to decrease postoperative pain scores, opioid consumption, and the incidence of PONV [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, interfascial plane blocks closer to epidural space, such as ESP and QL blocks, will likely have a visceral analgesic effect due to epidural spread. However, their visceral analgesic effect is still controversial [ 26 , 27 ], and several meta-analyses have reported a comparable analgesic effect between subcostal TAPB and other interfascial plane blocks [ 28 30 ]. Further, a recent meta-analysis reported that subcostal TAPB was associated with the greatest reduction in pain intensity at 12 hours postoperatively and PONV among various regional analgesic techniques [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can be performed at various levels, both thoracic and lumbar, depending on the type of surgery. Several studies have compared the efficacy of these techniques and the superiority of one among others with controversial results [9,10]. Nevertheless, we still do not have a current recommendation for the use of one technique over the others and the choice still relies on the on-duty anesthetist.…”
Section: Introductionmentioning
confidence: 99%